Can Ultrasound Guided Regional Anesthesia Improve Rural Anesthesia Services and Address Safety Issues in Low Income Country? Perspective from Nepal - Hamal, Pawan Kumar; Rayamajhi, Anuj Jung; Pokhrel, Nabin; Yadav, Rupesh Kumar; Bhattarai, Prajjwal Raj; Bista, Navindra Raj (Journal of Nepal Health Research Council, 2020)
Provision of anesthesia services in a deprived area particularly in low income countries is a major challenge all over the globe. Along with issues of manpower, logistics, services, there lies agendas of safety and accuracy while delivering the services. With rise in ultrasound use in regional anesthesia, pain and perioperative care, it is prudent that some of these issues can be addressed with proper training, mentoring and monitoring. The global idea needs to be implemented locally to reach out to huge volume of patients who are inadequately treated for the various painful conditions. A group of regional enthusiasts from Nepal takes the vision and mission in Nepalese context to address the issues. Keywords: Low income country; rural anesthesia; safety; ultrasound guided regional anesthesia